2017
DOI: 10.15406/jpcpy.2017.07.00430
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Emotional Intelligence in Teaching: Comparison between Practitioners from the United Kingdom & India

Abstract: Evidence demonstrates that an increase of emotional intelligence levels leads to work productivity and effectiveness. Within this study, emotional intelligence levels were examined for United Kingdom and Indian teacher practitioners. Teacher practitioners were instructed to complete a self-report measure of emotional intelligence following email contact. Results demonstrate that cross-cultural emotional intelligence scores were moderately high for teacher practitioners of the United Kingdom and India. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
(33 reference statements)
2
3
0
2
Order By: Relevance
“…In line with other studies (Gill and Sankulkar, 2017;Valente, 2019), a positive correlation also arose between gender and EI, with the EI being greater in women than in men (hypothesis 1). This finding provides empirical support for a gender difference in EI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with other studies (Gill and Sankulkar, 2017;Valente, 2019), a positive correlation also arose between gender and EI, with the EI being greater in women than in men (hypothesis 1). This finding provides empirical support for a gender difference in EI.…”
Section: Discussionsupporting
confidence: 91%
“…Variables such as gender, teaching experience, and academic training impact teachers' EI, and studies have shown that women generally score higher on EI measures than men (Gill and Sankulkar, 2017;Valente, 2019). Also, teachers with more advanced degrees (e.g., Ph.D.) tend to have higher EI levels (Sousa, 2011;Fernandes, 2015;Valente, 2019).…”
Section: Emotional Intelligence In the Classroommentioning
confidence: 99%
“…Similar to other studies (Gill & Sankulkar, 2017;Valente, 2019), the results have showed that gender was a statistically positive correlation with EI capacities (PUE: r = 0.156; p <0. 01; ECE: r = 0.095; p <0.…”
Section: Discussionsupporting
confidence: 89%
“…Studies analyze the role of personal and professional variables (e.g., gender, service time and academic formation) whit school teacher's EI. Some of these studies reveal high overall EI scores for women compared to men (Gill & Sankulkar, 2017;Valente, 2019). About the influence of service time on teacher's EI, some studies with Portuguese teachers indicate that teachers with more service time tend to have lower levels of EI (Sousa, 2011;Valente, 2019).…”
Section: Teacher's Emotional Intelligence Capacitiesmentioning
confidence: 99%
“…Some studies have analyzed the role of sociodemographic variables (e.g., gender, service time, and academic formation) of teachers in EI. These studies reveal high overall EI scores for females compared with males (Anari, 2012;Gill & Sankulkar, 2017;Sangeetha, 2017).…”
mentioning
confidence: 79%